Preparation and evaluation of an edible coating for tomato tree Cyphomandra betacea cav. Sendt post-harvest conse - Andrade Ch., Johana; Acosta A., Diana; Bucheli J., Mauricio; Luna C., Gloria Cristina (Revista de Ciencias Agrícolas, 2014)
In the department of Nariño, considerable losses in fruit quantity and quality, as well as vegetable production are estimated, due to the short shelf life greatly generated by the absence of protective systems. This has led to a low competitiveness of the value chain, severely limiting the region’s development and directly affecting the producers’ economy. Therefore, the viability of using bayberry Morella pubescens (H & B-Wilbur ex Willd) as raw material for the preparation of an edible coating in order to prolong fruit-life was evaluated. Nine formulations were studied in order to determine the most suitable coating, maintaining a constant amount of wax and additives used, and assessing the proportion of starch and water, using a 32 factorial response surface design, which allowed optimizing the formulation through the analyses. Tomato tree quality with the obtained coating was tested physicochemically and the results were analyzed, using an experimental design of a categorical factor by comparing samples through the Fisher mean difference. The statistical analysis showed a better performance in weight loss, transpiration, firmness, maturity index, and respiration in the coated samples with respect to the controls, as showed by a 25% increase in tomato tree lifetime; thus demonstrating the feasibility of bayberry as a component of edible coatings.